Some general aspects of thin-shell wormholes with cylindrical symmetry - Eiroa, Ernesto Fabian (2010)
In this article we study a general class of nonrotating thin-shell wormholes with cylindrical symmetry. We consider two physically sound definitions of the flare-out condition and we show that the less restrictive one allows for the construction of wormholes with positive energy density at the throat.We also analyze the mechanical stability of these objects under perturbations preserving the symmetry, proving that previous results are particular cases of a general property. We present examples of wormholes corresponding to Einstein-Maxwell spacetimes.